Writing a Script for a Short Video Promotion of Dapoer Cinta as a Culinary Destination in Palembang - Fadlurrahman, Fariz (Politeknik Negeri Sriwijaya, 2023)
ABSTRACT: The purpose of this study was to find out how to write a script for a short video of Dapoer Cinta to promote one of the culinary destinations in Palembang. Using a Research and Development (R&D) method adapted from Plomp (1997), with a qualitative descriptive design, the steps in designing the script were (1) preliminary investigation; (2) designing; (3) realization/development; (4) testing, evaluation, and revision; and (5) implementation. The data collection techniques were literature studies, observations, and interviews. Then, the data analysis was carried out through a qualitative descriptive method. There were 3 experts selected purposively to participate in revising the script: an Indonesian language expert, writing style expert, and an English expert. The data revealed that to produce a good promotional short video script, each expert suggested the following revisions. The Indonesian language expert recommended to revise the selection of words that were appropriate to PUEBI. Then writing style expert suggested to remove inappropriate sentences, and to change some sentences to be more efficient. Next, the English language expert suggested to revise grammatical errors, sentence structure, inappropriate use of transition signals, and inappropriate sentence changes. Finally, after the final text was approved and there were no further revisions, the script could be used as a short video script to promote Dapoer Cinta as a culinary destination in Palembang. Keywords: culinary tourism, promotion, short video